Marzena Machoś: Short lingual frenulum in newborns and infants diagnosis and treatment GooGoo 2020 Publishing - Cholewa, Marta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Marzena Machoś: Short lingual frenulum in newborns and infants diagnosis and treatment GooGoo 2020 Publishing